Rockingham, John Meredith: my Army recollections (June 16, 1979) - Rockingham, John Meredith, b. 1911; Main, Chris D. (1979)
An interview/narrative of John Meredith Rockingham's experiences during World War II and the Korean War. Major-General Rockingham, C.B., C.B.E., D.S.O. served with the Canadian Scottish Regiment and the Royal Hamilton Light Infantry. Interview took place on June 16, 1979.; ABSTRACT: Maj.-Gen. John Meredith Rockingham, C.B., C.B.E., D.S.O. Canadian Scottish Regiment Royal Hamilton Light Infantry